A Sociological Approach to the Extremist Radicalization in Islam: The Need for Indicators. Issue 1 (2nd January 2019) - García Magariño, Sergio; Talavero Cabrera, Víctor
ABSTRACT: This paper examines the factors connected with the Islamist radicalization process looking at three categories of indicators – psychological, meso-sociological, and macro-sociological ones –, in order to underline the need for designing early prevention and identification mechanisms. The proposal that these mechanisms should be at the heart of public policies to combat Islamist terrorism within the Spanish territory is one of the underlying assumptions from which this study has been undertaken. Defense policies are crucial, yet, when implemented without a profound understanding of the phenomenon being faced, might generate greater threats and spur the radicalization processes 1 in the long term. Provided that jihadist terrorists constitute a global reticular network, the sociological lens through which this whole paper views this topic, despite being underpinned in Spain, will draw on insights produced abroad.